Az iskolai zaklatás körforgása: Az iskolai zaklatás és az osztálylégkör kapcsolatának vizsgálata 12-14 évesek körében - Berta, Renáta; Dombi, Edina (Magyar Pedagógia, 2017)
This research aimed to explore the phenomenon of school bullying among primary school students. We aimed to show how their roles in bullying situations determine their well-being and how bullying affects the classroom atmosphere. The participants in this self-report study were sixth-, seventh- and eighth-grade students, who completed two questionnaires: the school bullying (Figula, n.d.) and class atmosphere (Dalbert & Stöber, 2002/2007) scales. A total of 110 students (Ngirl = 52; Nboy = 58) were involved in the study from two different primary schools: 44 sixth-graders, 38 seventh-graders and 28 eighth-graders. Their mean age was 13 years (SDage = 13.01; 0.96). Our results show that the number of boys among abusers is higher and that girls are more likely to be victims or bystanders. With regard to class atmosphere, victims feel the least comfortable in class, while bystanders feel the most comfortable. There is a changing dynamic in each class on the basis of different roles students play in bullying situations; it would therefore be very important for teachers to be familiar with the characteristics of these roles and the consequences of bullying.